2008
DOI: 10.1021/ef700520f
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Glycerol to Hydrogen via a Steam Reforming Process over Nickel Catalysts

Abstract: A glut of inexpensive glycerol has resulted from expanding biodiesel production around the world. This glycerol could be used as a good renewable source to produce hydrogen fuel. Hydrogen production from glycerol via a steam reforming process over Ni/CeO2, Ni/MgO, and Ni/TiO2 catalysts was studied. The catalysts were characterized by using X-ray diffraction, thermogravimetric analysis, BET surface area analysis, metal dispersion, active surface area analysis, and hydrogen temperature programmed reduction. Ni/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 25 publications
1
86
0
5
Order By: Relevance
“…Reforming reactions are generally highly endothermic, and a catalyst is often required to accelerate the reactions and favour hydrogen production in the reforming process (Adhikari, et al, 2008). The catalytic steam reforming of glycerol for hydrogen production involves complex reactions but these can be summarised by the mechanism outlined as follows.…”
Section: Reactions and Formulae For The Data Analysesmentioning
confidence: 99%
“…Reforming reactions are generally highly endothermic, and a catalyst is often required to accelerate the reactions and favour hydrogen production in the reforming process (Adhikari, et al, 2008). The catalytic steam reforming of glycerol for hydrogen production involves complex reactions but these can be summarised by the mechanism outlined as follows.…”
Section: Reactions and Formulae For The Data Analysesmentioning
confidence: 99%
“…Thus efforts on utilization of this abundant and cheap resource for the production of hydrogen or synthesis gas have been increasingly appearing in the literature [42]. Several investigations on thermodynamic and catalytic investigations on the steam reforming of glycerol (SRG) have been reported [43][44][45][46][47][48][49][50]. Table 2 lists the outcomes of various investigations in terms of hydrogen yield, selectivity and molar composition in the SRG.…”
Section: Steam Reforming Of Glycerolmentioning
confidence: 99%
“…Adhikari et al [47] investigated the effect of catalyst support in SRG with S/G between 6 to 12 and the temperature range 823-923 K with varying feed flow from 0.15 to 0.45 ml/min. They reported Ni/CeO 2 as the best catalyst in SRG as compared to Ni/MgO and Ni/TiO 2 .…”
Section: Catalytic Investigationsmentioning
confidence: 99%
“…They recommended that the syngas could be used as a fuel for fuel cells. Additionally, Adhikari et al [6] found that the maximum hydrogen yield was obtained at 650°C with MgO as a supported catalyst. Valliyappan [7] found that the maximum hydrogen production of 68.4% was produced from glycerol gasification using Ni/Al 2 O 3 catalyst at a temperature of 800° C and steam to glycerol ratio of 25:75.…”
Section: Introductionmentioning
confidence: 99%